INCLUSIVE FINANCIAL SYSTEM: A REVIEW OF EMERGING ISSUES FOR NIGERIA - Omoke, Philip Chimobi (EBSU Journal of Social Sciences and Humanities, 2022)
Monetary authorities’ solution to financial exclusion in Nigeria is through microfinance banks, this paper looks at the concepts of financial exclusion, factors affecting access to financial services, cost, causes and consequences of financial exclusion. The paper also looks at the emerging issues in financial exclusion and why microfinance as a panacea for financial exclusion will not work in Nigeria. We recommended the intervention of government both as facilitator and legislator to tackle the problem of financial exclusion in Nigeria.